2020
DOI: 10.21873/anticanres.14522
|View full text |Cite
|
Sign up to set email alerts
|

Methylsulfonylmethane Induces Cell Cycle Arrest and Apoptosis, and Suppresses the Stemness Potential of HT-29 Cells

Abstract: Background/Aim: Colorectal cancer is one of the most common malignancies worldwide. Small moleculebased chemotherapy is an attractive approach for the chemoprevention and treatment of colorectal cancer. Methylsulfonylmethane (MSM) is a natural organosulfur compound with anticancer properties, as revealed by studies on in vitro models of gingival, prostate, lung, hepatic, and breast cancer. However, the molecular mechanisms underlying the effects of MSM in colon cancer cells remain unclear. Materials and Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…Flow cytometry was used to assess the apoptotic status of cells following treatment with different drugs. It has been reported that the sub-G 1 phase is characterized by apoptosis induction (69). The proportion of cells in sub-G 1 phase was significantly increased following treatment with the combination of 15 µM UA + 1.5 µM DOX compared with the control and either agent alone (Figs.…”
Section: Ua Enhances Dox-mediated Inhibition Of Crc Cell Proliferationmentioning
confidence: 82%
“…Flow cytometry was used to assess the apoptotic status of cells following treatment with different drugs. It has been reported that the sub-G 1 phase is characterized by apoptosis induction (69). The proportion of cells in sub-G 1 phase was significantly increased following treatment with the combination of 15 µM UA + 1.5 µM DOX compared with the control and either agent alone (Figs.…”
Section: Ua Enhances Dox-mediated Inhibition Of Crc Cell Proliferationmentioning
confidence: 82%
“…MSM is a natural sulfur-containing compound with a well-known anticancer activity against various cancer cells in vitro and in vivo. Some studies have shown that it can inhibit the tumorsphere formed by colorectal cancer cells [ 30 ] and suppress stem cell marker protein expression in breast cancer tissue [ 36 ]. Considering the high dose of MSM, it has already been tested as nontoxic in normal cells and animal models, and up to a concentration of 6–8 g/kg/day through oral administration, mice remained healthy and vigorous [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…This compound exerts various physiological activities, including antioxidant and anti-inflammatory activities [ 26 , 27 ]. MSM is well known for its anticancer activity against various cancer types, including breast [ 28 ], lung [ 29 ], colorectal [ 30 ], and gingival cancers [ 31 ]. This MSM can also synergize chemotherapeutic drug activity to increase efficacy and reduce the adverse effect caused by the chemotherapeutic drug [ 32 , 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, other relevant studies have found that MSM can also block G0/G1 cell cycle progression. Studies showed that 200 mmol/L MSM can reduce or inhibit cell viability by inducing apoptosis and cell cycle arrest in the G0/G1 phase, such as prostate cancer (PC) cells, HT-29 cells, and gingival cancer cells (Nipin et al 2017;Kowalska et al 2018;Kim et al 2020). It was found that the regulation of MSM on the cell cycle is closely related to cyclin and proapoptotic proteins, such as cyclin D, cyclin E, and Bax (Kowalska et al 2018).…”
Section: Disscusionmentioning
confidence: 99%